Understanding the periodic table - Gardner, Jane P. (Chemistry of everyday elements., 2018)
Presents the history of the periodic table of the elements. Also discusses the format of the table and the ways in which different scientists use the table. Includes text-dependent questions, a glossary, and resources for further information.